The Reflection of Mongolian Linguistic and Cultural Characteristics in Contemporary Literature: (A Study of the Poem “Gazar shoroondoo bi khairtai” by the Sh. Dulmaa) - Ragchaa, Bigermaa (Mongolian Language and Literature Studies, 2025)
The distinctive features of Mongolian national culture and mentality are closely intertwined with their traditional pastoral economy, nomadic civilization, and harmonious relationship with nature. Mongolians are a great people who have preserved and contributed a unique cultural identity to the global treasury of human civilization and intellectual heritage. This distinctive cultural and traditional character of the Mongols has been transmitted to future generations through their literature and artistic expression.In this paper, we aim to explain how the language and culture of Mongolians are reflected in modern literature, especially in poetry, with the example of the poem "Gazar shoroondoo bi khairtai" by Sh. Dulmaa (1934-2024). Монголчуудын хэл, соёлын онцлог орчин үеийн уран зохиолд илэрсэн нь (Ардын уран зохиолч Ш.Дулмаагийн “Газар шороондоо би хайртай” шүлгийн жишээгээр) Хураангуй: Монгол үндэсний соёл, сэтгэлгээний онцлог нь тэдний эрхэлж ирсэн мал аж ахуй, нүүдлийн соёл иргэншил, байгаль орчинтой харьцах харьцаа, хандлагатай нягт холбоотой бөгөөд монголчууд дэлхийн хүн төрөлхтний соёл судлал, оюун сэтгэлгээний санд өөрийн гэсэн өвөрмөц соёлыг дархлан үлдээж ирсэн агуу ард түмэн билээ. Монголчуудын соёл, зан заншлын энэ өвөрмөц онцлог тэдний уран зохиолоор дамжин, үр хойчдоо уламжлагдан ирдэг. Энэхүү өгүүлэлдээ бид монголын орчин үеийн уран зохиолд монгол соёл, зан заншлын онцлогийг хэрхэн тусгасан тухай “Ардын уран зохиолч”, яруу найрагч Ш.Дулмаагийн (1934-2024) "Газар шороондоо би хайртай" шүлгийн жишээгээр тайлбарлахыг хичээлээ. Түлхүүр үгс: Бичгийн уран зохиол, яруу найраг, уламжлал, бэлгэдэл, зан заншил, байгаль хамгаалах, цээрлэх ёс